PENGARUH MODEL PROJECT BASED LEARNING BERBANTUAN MEDIA AUDIOVISUAL TERHADAP KETERAMPILAN MENULIS TEKS BERITA SISWA KELAS VII SMP NEGERI 41 PADANG - Zahra, Laina; Yulianti Rasyid; Dadi Satria; Dewi Anggraini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Project Based Learning model assisted by audiovisual media on students’ news writing skills. This research used a quantitative approach with a pre-experimental method and a one group pretest-posttest design. The population consisted of 113 seventh-grade students of SMP Negeri 41 Padang, while the sample was class VII E with 26 students selected using purposive sampling. The data were in the form of students' scores before and after the implementation of the model. The results showed that students' writing skills before treatment were in the sufficient category with an average score of 64.42, while after treatment they improved to the good category with an average score of 73.24. The t-test results indicated that the alternative hypothesis was accepted at a 95% significance level. Therefore, it can be concluded that the Project Based Learning model assisted by audiovisual media has a significant effect on improving students' news writing skills.